History of Human Thought Knowing God - Syarifuddin Syarifuddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this study to find out the history of human thought knowing god. The result of this study The scientific content in the word of God which is owned by the belief of understanding the divinity of religious people, should be the responsibility of Muslim scientists to make it a scientific answer, to those who need it, including all children of the nation of different religions in life who are bound by the one God values. Currently, the interest of preaching and scientific seminars must be able to inspire, and change the mindset of people from not having their hijab open to God, to being able to open their veils to God, not to blaspheme and corner other people, especially those who are not of the same religion. Or in other words, it must be able to shift the soul of a believer into a pious person's soul instantly, with a strand of contemporary language, where in the language of da'wah. By having a good and correct divine science, it is clear that religion is nothing but composed of conceptually real laws like the universe which consists of nothing but the laws of physics, chemistry and biology. It's just that the dignity and dimensions of these religious laws are higher and are essential, absolute and if viewed philosophically it appears that this nature is very perfect. Divine philosophy teaches us how to utilize and apply both physical and spiritual aspects and how to conform to God's plan, and reveal the true purpose of life. In fact, as seen from a spiritual point of view, life has no division: life is one, as is constantly. There is no death, only constant change.